Tool wear and resulting surface finish during micro slot milling of polycarbonates using uncoated and coated carbide tools. (January 2020) - Jahan, Muhammad Pervej; Ma, Jianfeng; Hanson, Craig; Arbuckle, Greg K
A growing application of polycarbonates is in the microfluidic disks and DNA detection devices, where surface finish of the micro-channels plays an important role. This study intends to investigate the tool wear and surface finish generated during micro slot milling of polycarbonate using uncoated, TiN-coated, and TiAlN-coated tungsten carbide tools. The effects of tool coating and the machining parameters on the possible reduction of tool wear and improvement of surface finish were investigated. It was found that with careful selection of cutting parameters and tool coating, micro-channels with smoother surface finish, minimum burrs around the edges, and controlled tool wear can be obtained using micro-milling. A combination of medium range of depth of cut and feed rate was found to improve the surface finish in polycarbonates, as well as minimize the tool wear. The TiAlN tool coating was found to only be effective in reducing tool wear without much effect on the machined surface. The adhesion was found to be the most dominating tool wear mechanism in uncoated carbide tool, followed by cutting edge chipping and tool nose's plastic failure. The adhesion wear was found to be reduced in coated tools, especially in TiAlN-coated tools, although delamination wear started to dominate in the coated tools when higher feed rate and depth of cut were used. Both lower and higher of depths of cut were found to generate higher tool wear and leave traces of tool marks on the machined surface.